Multicultural education and formation of ethnic tolerance of children in preschool educational establishments of Zakarpattia (Training and Practice : Journal of Educational Sciences, 2018)
Zakarpatia is a multinational land, alongside with each other live Ukrainian, Hungarian, Romanian, Russian, Roma, Slovak, German people and other national minorities; it is what makes this land unique. From the remote times, the issues of national, multicultural, patriotic education, formation of positive, tolerant attitude towards the representatives of different nationalities have been relevant on the territory of the land. At the age of 4 a child shows the first signs of ethnic identity, it is reasonable at this age to start working on formation of ethnic and confessional tolerance.Our goal is to educate a person, who, preserving the social and cultural identity, aspires to understand other cultures, respects other cultural and ethnic similarities, is able to live in peace and harmony with the representatives of different nationalities, races, beliefs. The experience of multicultural education and tolerant coexistence of preschool-age children in preschool educational establishments of Zakarpatia have been revealed in the publication.